THE INFLUENCE OF BIG FIVE PERSONALITY, SOCIAL SUPPORT, AND GENDER ON POST-TRAUMATIC GROWTH IN CENTRAL SULAWESI NATURAL DISASTER SURVIVORS - Diny Sri Marini; Siti Urbayatun; Nurul Hidayah (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Post-traumatic growth (PTG) is the positive growth of individuals after facing a life crisis due to a traumatic event. This study aims to determine the role of big five personalities, social support, and gender towards PTG of Central Sulawesi natural disaster survivors. This research uses the descriptive quantitative method. The participants in this study were 128 survivors of natural disasters in Central Sulawesi and adults, 43 males and 85 females. The instruments used in this study were the post-traumatic growth scale, the IPIP-BFM-25 Indonesia scale, and the social support scale. The data analysis technique used in this study was covariance analysis with SPSS 21.0 for windows software. This study indicates that big five personalities, social support, and gender play a role simultaneously and significantly towards PTG with coefficient F = 15,600 (p = 0,000; p < 0,01). Extraversion has a significant positive role in PTG with coefficient F = 20,760 (p = 0,000; p < 0,01), agreeableness has a significant positive role towards PTG with coefficient F = 50,506 (p = 0,000; p < 0,01), and conscientiousness has significant positive role in PTG with coefficient F = 1350,684 (p = 0,000; p < 0,01). This study shows the big five personalities, social support, and gender simultaneously have a role in the PTG development of natural disaster survivors. Emotional stability, intellect, social support, and gender do not have a direct role in PTG. Survivors have a high chance to reach PTG with high extraversion, agreeableness, and conscientiousness. Keywords: Big five personality, gender, post-traumatic growth, social support